2018
DOI: 10.1037/ppm0000124
|View full text |Cite
|
Sign up to set email alerts
|

Play to win over: Effects of persuasive games.

Abstract: Persuasive games are a subset of serious games that are getting increased attention from the gaming industry as well as researchers. Although their title implies they can be intuitively defined as having the primary intention of changing or reinforcing players' attitudes on certain topics, only a handful of studies have provided evidence that these games actually influence attitudes. After presenting a summary of previous studies' results, the current article expands on this evidence by reporting on a controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 18 publications
3
62
0
1
Order By: Relevance
“…Although strong effects of persuasive games have been found in some studies (Kampf & Cuhadar, 2014;Peng et al, 2010;Ruggiero, 2015), weaker effects have been found in other studies (Barthel, 2013;Gutierrez et al, 2014;Jacobs, 2016;Soekarjo & Van Oostendorp, 2015). Ultimately, however, there are too few empirical studies to derive conclusions on the genre as a whole.…”
Section: Interactivity and Construal Levelmentioning
confidence: 87%
See 3 more Smart Citations
“…Although strong effects of persuasive games have been found in some studies (Kampf & Cuhadar, 2014;Peng et al, 2010;Ruggiero, 2015), weaker effects have been found in other studies (Barthel, 2013;Gutierrez et al, 2014;Jacobs, 2016;Soekarjo & Van Oostendorp, 2015). Ultimately, however, there are too few empirical studies to derive conclusions on the genre as a whole.…”
Section: Interactivity and Construal Levelmentioning
confidence: 87%
“…In the academic literature, player-game interactions are described with multiple concepts that are sometimes similar and almost always related (Caroux et al, 2015;Wirth et al, 2007). Examples are engagement (Boyle, Connolly, Hainey, & Boyle, 2012), enjoyment (Jacobs, 2016), presence (Banos et al, 2004), and flow (Schmierbach, Chung, Wu, & Kim, 2014). Resolving this debate was not the aim of the present research, however.…”
Section: Immersion and Identification As Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected a game as a medium to deliver the experimental task since games are engaging and can keep the players' concentration high and prevent boredom during the 25 min of the experimental session (Jacobs, 2016;Lawson & Semwal, 2016). The task for this study is based on an online game called 'Smoothie Maker: Creation Station'.…”
Section: Taskmentioning
confidence: 99%